Effect of aneuploidy on cellular adaptation to hyper-osmotic and ionic stress - Natali, Federica (Nanyang Technological University, 2022)
Aneuploidy, the condition of having an impaired karyotype is a distinctive characteristic of cancer cells and has been proposed to promote cancer evolution by conferring drug resistance and aggressive phenotypes. At a cellular level, aneuploidy, by massively changing the transcriptome and the proteome, has a profound impact on cellular phenotype. Specifically, aneuploidy has negative effect on cellular fitness in normal growth conditions in which euploid cells are already optimized to live. However, when the growth conditions are unfavorable, different aneuploid strains showed improved growth in different environmental or genetic perturbations. Adaptive mechanisms were linked to upregulation of specific genes on the aneuploid chromosome, suggesting that cells with different karyotypes have different phenotypes and fitness potential. At the same time, aneuploidy has been shown to promote further chromosome and genetic instability that could lead to the generation of a genomically heterogeneous aneuploid populations. I therefore hypothesize that aneuploidy might increase cellular evolvability via two mechanisms: first aneuploidy increases genetic and karyotypic instability and therefore generates population of cells carrying different phenotypes. Second, each different karyotype is associated with a different set of phenotypes. Therefore, these two mechanisms combined increase phenotypic variation which ultimately leads to higher adaptive potential. The aim of my project, performed using the yeast S. cerevisiae, is to test if evolvability of euploid and aneuploid cellular populations correlates with their level of genomic instability, when cells are challenged with an environmental perturbation. For this purpose, a collection of isogenic euploid and aneuploid yeast strains containing simple and complex karyotypes has been evolved in different conditions through serial passages, and evolution has been assessed as deviation from initial ratio in competition experiments between strains of same ploidy tagged with two fluorophores.